Abordando los determinantes sociales de la salud: reapertura del debate y las implicaciones para la salud y el bienestar general de los colombianos (Avances en Enfermería, 2020)
Despite the fact that some disease-processes are linked to unmodifiable causes (e.g., biological sex, genetic or inheritable aspects), the health status of individuals and populations is highly dependent on the social, economic and psychosocial environments, the conditions in which people were born, and the experiences over their life-course. These factors are labeled as the social determinants of health (SDoH) or the “causes of the “causes” (1). SDoH include individual factors such as education, place of residence, employment status, income or housing, and aggregated factors such as access to transportation, quality of the health care system, public safety, social cohesion and support, and national and international trade policies (1, 2), which shape, directly and indirectly, the health outcomes and trajectories of individuals [Fragmento de texto]